Comparison of the Progression of High- and Low-tension Glaucoma as Determined by Two Different Criteria - Lee, Ji Yun (Korean J Ophthalmol, 2016)
PURPOSE: To investigate and compare the progression of medically treated primary open angle glaucoma according to the baseline intraocular pressure (IOP). METHODS: This study included a total of 345 eyes from 345 patients (mean follow-up period, 4.5 years). Eyes were classified into either conventional normal tension glaucoma (cNTG, ≤21 mmHg) or conventional high-tension glaucoma (cHTG, >21 mmHg) groups according to the conventional cut-off value of the IOP. Additionally, the median IOP (15 mmHg) was used to create two other groups (median NTG [mNTG] ≤15 mmHg and median HTG [mHTG] >15 mmHg). Using these values, 306, 39, 153, and 192 eyes were assigned to the cNTG, cHTG, mNTG, and mHTG groups, respectively. Glaucoma progression was determined either by optic disc/retinal nerve fiber layer photographs or serial visual field data. RESULTS: Mean reduction of IOP after medical treatment and of central corneal thickness was lower in the cNTG group, while the prevalence of disc hemorrhage and baseline visual field mean deviation did not differ between the cNTG and cHTG groups. A mean reduction in the IOP was observed after medical treatment, and central corneal thickness was lower in the mNTG group; disc hemorrhage was more frequent in the mNTG than in the mHTG group. Among the 345 analyzed eyes, 100 (29%) showed progression during the follow-up period. In the cHTG group, a higher baseline IOP (hazard ratio, 1.147; p = 0.024) was associated with glaucoma progression. Disc hemorrhage (hazard ratio, 15.533; p < 0.001) was also strongly associated with progression in the mNTG group. CONCLUSIONS: Baseline IOP was a significant risk factor for glaucoma progression in cHTG patients (10% of our total participants), while disc hemorrhage showed the strongest association with progression in the mNTG group, indicating that a cut-off value other than the conventional 21 mmHg is required to define true low-tension glaucoma in populations where NTG predominates among all glaucoma patients.